2021
DOI: 10.1071/fp20309
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of machine learning methods to improve estimation of ground coverage from unmanned aerial vehicle (UAV) imagery for high-throughput phenotyping of crops

Abstract: Ground coverage (GC) allows monitoring of crop growth and development and is normally estimated as the ratio of vegetation to the total pixels from nadir images captured by visible-spectrum (RGB) cameras. The accuracy of estimated GC can be significantly impacted by the effect of 'mixed pixels', which is related to the spatial resolution of the imagery as determined by flight altitude, camera resolution and crop characteristics (fine vs coarse textures). In this study, a two-step machine learning method was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…In recent years, unmanned aerial vehicles (UAVs) have become a popular field phenotyping platform for precision agricultural applications. UAV-based phenotyping is the measurement and analysis of plant characteristics in a far more advanced and detailed manner [23,24,[28][29][30][31][32][33][34][35]. UAVs mounted with very-high-resolution (VHR) cameras offer advanced crop image throughput analytics and are effective in overcoming the limitations of satellite imagery [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, unmanned aerial vehicles (UAVs) have become a popular field phenotyping platform for precision agricultural applications. UAV-based phenotyping is the measurement and analysis of plant characteristics in a far more advanced and detailed manner [23,24,[28][29][30][31][32][33][34][35]. UAVs mounted with very-high-resolution (VHR) cameras offer advanced crop image throughput analytics and are effective in overcoming the limitations of satellite imagery [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that, the higher the spatial resolution of the RGB UAV images for the assessment of flower cover, the higher the accuracy (through the goodness of fit) with the in situ flower cover and with the bee abundance, diversity and richness. This is probably largely the result of the fact that images with higher spatial resolution are better able to differentiate between flowers, grass or soil, offering higher information details and reducing the mixed pixel issue (Hu et al, 2021). Images with coarse spatial resolution result in mixed signal at pixel scale, integrating the spectral signature of various vegetative organisms (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we aim to assess flower cover as a proxy for bee abundance using images from a UAV. The fundamental step in estimating flower cover is distinguishing flower pixels from grass or soil pixels by means of differences in the spectral signatures (Hu et al, 2021). Different types of images can be used for this purpose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unmanned aerial vehicle (UAV) based remote sensing is flexible in data acquisition regarding diverse sensors as well as spatial and temporal resolutions [7,9]. Given the growing demand for high-throughput phenotyping to support crop breeding, great interest has been expressed in using UAV-based platforms to rapidly and non-destructively collect phenotypic data (e.g., imagery) under field conditions [9][10][11]. UAV-based high-throughput phenotyping usually estimates crop traits through the integration of UAV-derived vegetation indexes (VIs) with statistical models [12].…”
Section: Introductionmentioning
confidence: 99%